(POST)ČLOVEK (POST)ČLOVEKU VLKOM: PROBLÉMY PRIATEĽSTVA AKO KOHÉZNEHO PRVKU V SPOLOČNOSTI POSTĽUDÍ. - DUDÍKOVÁ, PATRÍCIA (Filozofia, 2022)
The paper examines the possibilities of friendship in transhumanist ideas of society of posthumans. Some transhumanists claim that human enhancement through technologies will also lead to a better and more cohesive society. The presented article challenges this claim by showing that transhumanist theories rather omit the social aspects of humans and their expectations about posthuman society are not really convincing. In the article, I focus on a specific type of transhumanism - so called extropianism, which emphasizes individual's own responsibility, autonomy and motivation for self-improvement. The article itself is divided into three parts. In the first part I present extropianist ideas of posthuman as a result of human enhancement. In the second part I think about those ideas in the context of the whole society of posthumans. The third part focuses on friendship as a phenomenon that can bring individuals close together and increase the degree of solidarity and cooperation. I consider the possibilities of existence of such relationship in a future society of posthumans.